Utilization of Immunohistochemistry in Gynecologic Pathology: An Experience at a Tertiary Care Hospital, Lahore-Pakistan - Madiha Iqbal, Rabia Basharat, Farah Kalsoom, Asmaa Qureshi, Qurat Ul Javaid, Farrukh Kamal, Rubina Farrukh, Khawaja Moeen Ud Din, Muhammad Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Immunohistochemistry is an adjunct tool in Surgical Pathology. The fast growing use of immunohistochemistry in gynecologic Pathology has revolutionized the fields of tumor diagnostics & research. Objective: The objective of the study was to share & discuss the experience of utility of immunohistochemistry in Gynecologic Pathology, at a tertiary care hospital in Lahore, Pakistan. Patients & Methods: This was a retrospective, descriptive, cross sectional study, carried out at the Pathology Department of Fatima Jinnah Medical University, Lahore. All cases which were diagnosed after the application of immunohistochemistry during the study period from 1st July 2019 to 31st December 2020 were included in the study. Data included age of the patient, marital status, parity, clinical & radiological presentation, histopathological findings & differentials, list of immunohistochemical markers applied to the case with results & final histopathological diagnosis. Data was analyzed using SPSS version 17. Results: A total of 196 cases were included in the study. The age of the patients ranged from 14 years to 82 years with a mean age of 41 ± 7 years. The commonest use of immunohistochemistry was for histological classification of the tumors of the female genital tract, identifying precancerous lesions, differentiating primary from metastatic CA & predicting response to chemotherapy via proliferative index Ki67. The most commonly used immunohistochemical markers were CK, CK7, CK20, CD 3, CD20, ER, PR, VIMENTIN, WT 1, Ki67, CD 117, SMA, INHIBIN, p53 & p63. Practical implication This study shares the experience of use of common immunohistochemical markers in different cases of gynecologic pathology, highlighting & discussing different panels for use in different scenarios, from which other pathologists may benefit. Conclusion: Immunohistochemistry is an important ancillary tool in the evaluation of gynecologic pathology cases. However, it cannot replace conventional histopathology. It should always be used as an adjunct to histopathology, in the proper clinical & radiological context. Keywords: immunohistochemistry, gynecologic pathology, ovarian carcinoma, leiomyoma, dysgerminoma,